178k views
4 votes
What is the solution of the system? y = 13x - 1 ; y = 9x + 4

User Jbnunn
by
5.5k points

1 Answer

6 votes

Answer:


((5)/(4),(61)/(4))

Explanation:

This system we can solve by substitution method :

y=13x-1

y=9x+4

_______

y=13x-1

13x-1=9x+4 (instead y in second equation we use 13x-1 and first rewrite)

_______

y=13x-1

13x-9x=4+1 (subtract 9x and add 1 for each side)

______

y=13x-1

4x=5 (divide by 4)

_____

y=13x-1


x=(5)/(4) (instead x in first eq we write 5/4)

______


y=13*(5)/(4) -1=(65-4)/(4)=(61)/(4)

User Yeison
by
6.0k points